Factors associated with the use of Dental Health Services by Mexican Schoolchildren to receive Professionally Applied Topical Fluoride - Cerón-Zamora, Eduardo; Navarrete-Hernández, José de Jesús; Lara-Carrillo, Edith; Robles-Bermeo, Norma Leticia; Lucas-Rincón, Salvador Eduardo; Hernández-Martínez, César Tadeo; López-Pontigo, Lydia; Villalobos-Rodelo, Juan José; Medina-Solís, Carlo Eduardo (Puerto Rico Health Sciences Journal, 2020)
Objective: To identify the prevalence of and factors associated with the use of dental health services to receive professionally applied topical fluoride (DHSU-PATF) in the 12 months prior to the study among Mexican schoolchildren aged 6 to 12 years. Methods: A cross-sectional study was performed in 1,404 schoolchildren selected randomly from 15 public schools in the city of Pachuca, Mexico. Questionnaires were distributed to determine the demographic, socioeconomic, and behavioral variables. The dependent variable was the DHSU-PATF in the year before the study, which was dichotomized as 0 (no DHSU-PATF) or 1 (yes, DHSU-PATF). We calculated odds ratios (OR) and 95% confidence intervals. The analysis was performed in Stata 11.0. Results: The prevalence of DHSU-PATF was 5.1%, but lower among younger children (OR = 0.86) and greater among children with health insurance (private insurance, OR = 3.64; insurance provided by the government owned oil company, the Army, or the Navy, OR = 5.03). The level of knowledge about oral health among guardians/ parents was also a factor (medium, OR = 2.37; high, OR = 4.05). Additionally, among the children whose parents/guardians perceived them (the children) as having good or very good oral health, the OR was 3.33; among children whose parents brushed their teeth with greater relative frequency, the OR was 8.74. Finally, DHSU-PATF was greater among children with relatively higher socioeconomic status (2nd quartile, OR = 3.29; 3rd quartile, OR = 5.99; 4th quartile, OR = 4.64). Conclusion: The receipt of PATF was low in this sample of Mexican schoolchildren and is associated with socioeconomic and behavioral factors. This gives us a guideline to create or improve topical fluoride application strategies in the public and private Mexican health systems.